تطور نشاط الأحزاب المغربية في منطقة الحماية الفرنسية - تامة, عبد القادر; مراح (جامعة الوادي - University of Eloued, 2023)
يكتسي موضوع نشاط الأحزاب المغربية في المنطقة الفرنسية أهمیةكبیرة،حیث يعتبر من أهم المواضیع ا لتي تطلعنا على جانب مهم من وقائع تاريخ المغرب الأقصى قبل الاستقلال ، وذلك من خلال الكشف على جوانب عديدة منكفاح الشعب المغربي، وأثرهالمباشر في تحقيق الحرية ، ونهدف من خلال هذه الدراسة إلى تسلیط الضوءعن أهم المحطات التاريخية التي برز فيها نشاط الأحزاب المغربية،وهي الفترة الممتدة بين سنتي 1944و1956، لنبين أساليب النضال الوطني لهذه الأحزاب ودورها السياسي والعسكري في تحقيق الاستقلال . Abstract The subject of the activity of Moroccan parties in the French region is of great importance، as it is considered one of the most important topics that inform us of an important aspect of the history of Morocco before independence، by revealing many aspects of the struggle of the Moroccan people، and its direct impact on achieving freedom، and we aim through this study to shed light on the most important historical stations in which the activity of Moroccan parties emerged، which is the period between 1944 and 1956، to show the methods of national struggle of these parties And its political and military role in achieving independence.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: نشاط الاحزاب ، المغرب الاقصى، الحماية الفرنسية; The activity of the parties, Al-AqsaMorocco, the French protectorate